The Rise and Decline of ISIS: An Analysis of the Islamic State's Genesis, Expansion, and Demise - Louis Shawn (International Journal of Science and Society, 2023)
The Islamic State of Iraq and Syria (ISIS), also known as the Islamic State (IS), emerged as a formidable extremist organization with global implications in the early 21st century. This article aims to provide a comprehensive analysis of ISIS's origins, expansion, and eventual decline. It explores the ideological underpinnings of ISIS, its territorial conquests, recruitment strategies, and counterterrorism efforts by the international community. By examining the multifaceted aspects of the group's rise and fall, this study contributes to a deeper understanding of the challenges posed by transnational terrorist organizations and the strategies employed to combat them.